Tuning the modular Paracoccus denitrificans respirome to adapt from aerobic respiration to anaerobic denitrification. (4th December 2017) - Giannopoulos, Georgios; Sullivan, Matthew J.; Hartop, Katherine R.; Rowley, Gary; Gates, Andrew J.; Watmough, Nicholas J.; Richardson, David J.
Summary: Bacterial denitrification is a respiratory process that is a major source and sink of the potent greenhouse gas nitrous oxide. Many denitrifying bacteria can adjust to life in both oxic and anoxic environments through differential expression of their respiromes in response to environmental signals such as oxygen, nitrate and nitric oxide. We used steady‐state oxic and anoxic chemostat cultures to demonstrate that the switch from aerobic to anaerobic metabolism is brought about by changes in the levels of expression of relatively few genes, but this is sufficient to adjust the configuration of the respirome to allow the organism to efficiently respire nitrate without the significant release of intermediates, such as nitrous oxide. The regulation of the denitrification respirome in strains deficient in the transcription factors FnrP, Nnr and NarR was explored and revealed that these have both inducer and repressor activities, possibly due to competitive binding at similar DNA binding sites. This may contribute to the fine tuning of expression of the denitrification respirome and so adds to the understanding of the regulation of nitrous oxide emission by denitrifying bacteria in response to different environmental signals.